229k views
4 votes
Solve for f. 6f + 9g = 3g +f

1 Answer

4 votes

Answer:


f=-(6g)/(5)

Explanation:

Given:
6f + 9g = 3g +f

To solve for the value
f, we need to isolate it on one side of the equal sign. Let's move the
f on the right side to the left side by subtracting it from both sides. We then get:


5f + 9g = 3g

Subtract
9g from both sides of the equal sign to isolate the
5f.


5f= -6g

To solve for
f, we need to divide both sides by
5 since it is being multiplied by
f.


(5f)/(5) =(-6g)/(5)\\f=-(6g)/(5)

User Josh Smeaton
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.